Haematology and Antibacterial Properties of Blood from Horseshoe Crabs (Carcinoscorpius Rotundicauda and Tachypleus Gigas) - Zadeh, Shahram Shakiba (2006)
Samples of adult Carcinoscorpius rotundicauda and Tachypleus gigas caught from Pulau Lumut, Selangor, were conditioned in the Hatchery Unit, Universiti Putra Malaysia and used for all the experiments. Haematological study of the C. rotundicauda and T. gigas was carried out by blood extraction through cardiac puncture. Light microscopy of blood from both species showed the existence of only one type of blood cell, granulocyte, circulating in their circulatory system. Blood cell count for C. rotundicauda and T. gigas were not significantly different (27,000 and 33,000 cells/mm3, respectively), but it was otherwise for the two sexes of C. rotundicauda. Blood cell measurements of both species revealed that the size of T. gigas blood cells were significantly larger than C. rotundicauda. Transmission electron microscopy of blood cells was carried out for normal and clotted blood of both species. Granulocytes contained of all the necessary organelles: a nucleus, Golgi apparatus, mitochondria, endoplasmic reticulum, ribosome particles, vacuoles, and microtubles. Moreover two types of granules filled the cytoplasmic space, they were large and small granules. Intermediate stages of granules were observed in the cytoplasmic region especially near the Golgi apparatus. Light microscope photography of the degranulation process of granulocytes with one minute interval in both species exhibited similar pattern. Blood cells under un-sterile condition released their granules which are the main source of the immunologic material. Vacuoles with different sizes then filled the cytoplasmic space and at the same time cytoplasmic projections were formed.